The Kindle: A Novel Way to Increase Access to Medical Information in Community Clinics - Grigg, Karen; von Isenburg, Megan; Thibodeau, Patricia L.; Tuttle, Brandi (2009)
Poster presented at 2009 Medical Library Association (MLA)